M mbrez2 Jan 2016 7 0 USA Jan 24, 2016 #1 Assume that g(x)=(x-2)/(x+2). Simplify the expression [g(x)-g(9)]/x-9.
skeeter MHF Helper Jun 2008 16,217 6,765 North Texas Jan 24, 2016 #2 $g(x) = \dfrac{x-2}{x+2}$ $\dfrac{g(x)-g(9)}{x-9} = \dfrac{\dfrac{x-2}{x+2} - \dfrac{7}{11}}{x-9}$ start by multiplying numerator & denominator by $11(x+2)$ to clear the fractions ... $\dfrac{\dfrac{x-2}{x+2} - \dfrac{7}{11}}{x-9} \cdot \dfrac{11(x+2)}{11(x+2)} =\dfrac{11(x-2) - 7(x+2)}{11(x+2)(x-9)}$ simplify the numerator, factor the result, then you should see a cancellation. Reactions: 1 person
$g(x) = \dfrac{x-2}{x+2}$ $\dfrac{g(x)-g(9)}{x-9} = \dfrac{\dfrac{x-2}{x+2} - \dfrac{7}{11}}{x-9}$ start by multiplying numerator & denominator by $11(x+2)$ to clear the fractions ... $\dfrac{\dfrac{x-2}{x+2} - \dfrac{7}{11}}{x-9} \cdot \dfrac{11(x+2)}{11(x+2)} =\dfrac{11(x-2) - 7(x+2)}{11(x+2)(x-9)}$ simplify the numerator, factor the result, then you should see a cancellation.